2021
DOI: 10.3390/microorganisms9071355
|View full text |Cite
|
Sign up to set email alerts
|

Sourdough Microbiome Comparison and Benefits

Abstract: Sourdough is the oldest form of leavened bread used as early as 2000 BC by the ancient Egyptians. It may have been discovered by accident when wild yeast drifted into dough that had been left out resulting in fermentation of good microorganisms, which made bread with better flavour and texture. The discovery was continued where sourdough was produced as a means of reducing wastage with little known (at that point of time) beneficial effects to health. With the progress and advent of science and technology in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 160 publications
(253 reference statements)
2
31
0
1
Order By: Relevance
“…Sourdough fermentation has a long tradition in the production of breads, and several studies indicate that the use of LAB as starter cultures and the resulting fermentation process offers the possibility to produce breads with beneficial effects on human health [ 49 ]. These positive health effects may result from the production of EPS, which is formed by LAB during the fermentation process [ 6 , 8 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sourdough fermentation has a long tradition in the production of breads, and several studies indicate that the use of LAB as starter cultures and the resulting fermentation process offers the possibility to produce breads with beneficial effects on human health [ 49 ]. These positive health effects may result from the production of EPS, which is formed by LAB during the fermentation process [ 6 , 8 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sourdough fermentation has a long tradition in the production of breads, and several studies indicate that the use of LAB as starter cultures and the resulting fermentation process offers the possibility to produce breads with beneficial effects on human health [ 49 ]. These positive health effects may result from the production of EPS, which is formed by LAB during the fermentation process [ 6 , 8 , 49 , 50 , 51 ]. Furthermore, the use of special β-glucan-producing LAB as starters in sourdough fermentation offers the possibility to naturally enrich breads and baked goods with β-glucan, to improve sensory and rheological properties and generate foods with an additional health-promoting value [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autochthonous microorganisms present in raw material (fruits, vegetables, grains) or starter cultures shape the organoleptic profile of the final products [ 78 ]. According to the previously stated definition, probiotics are living microbial cells, so this basic criterion for probiotics is often not met in fermented products due to technological conditions in which bacteria do not survive [ 79 , 80 ]. Moreover, bacteria considered as probiotics are well characterized, and their characteristics are assigned to the strain.…”
Section: Probioticsmentioning
confidence: 99%
“…Sourdough is a traditional starter culture, which is used in making steamed buns, bread, and many other artisanal sourdough-based baked foods with unique flavours throughout the world [1,2]. The complex microbioflora of sourdough including yeasts, lactic acid bacteria (LAB), and moulds, have different metabolic capabilities and nutritional needs [3].…”
Section: Introductionmentioning
confidence: 99%
“…When glucose, fructose and lactose were present as carbon sources, L. plantarum and S. cerevisiae stimulated each other. In addition, it was demonstrated that L. sanfranciscensis is stimulated by CO 2 and another yet-to-be-identified factor produced by yeast in a sourdough-like environment [19]. Recent research has found that the ratio of LAB to yeast may affect the overall flavour of fermented products by influencing the Maillard reaction [13].…”
Section: Introductionmentioning
confidence: 99%